2018
DOI: 10.7185/geochemlet.1829
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics contaminate the deepest part of the world’s ocean

Abstract: Millions of metric tons of plastics are produced annually and transported from land to the oceans. Finding the fate of the plastic debris will help define the impacts of plastic pollution in the ocean. Here, we report the abundances of microplastic in the deepest part of the world's ocean. We found that microplastic abundances in hadal bottom waters range from 2.06 to 13.51 pieces per litre, several times higher than those in open ocean subsurface water. Moreover, microplastic abundances in hadal sediments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
166
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(192 citation statements)
references
References 0 publications
5
166
1
5
Order By: Relevance
“…The term 'microplastics' refers to plastic particles of < 5 mm in size [2]. Their presence in the environment has been reported since the early 1970s [3], and many studies since have shown that microplastics are now ubiquitous in the oceans at all depths [4,5], from the Arctic [6] to the Antarctic [7]. Most studies have focused on microplastics in marine systems, with < 4% of publications concerning freshwater systems [8].…”
Section: Introductionmentioning
confidence: 99%
“…The term 'microplastics' refers to plastic particles of < 5 mm in size [2]. Their presence in the environment has been reported since the early 1970s [3], and many studies since have shown that microplastics are now ubiquitous in the oceans at all depths [4,5], from the Arctic [6] to the Antarctic [7]. Most studies have focused on microplastics in marine systems, with < 4% of publications concerning freshwater systems [8].…”
Section: Introductionmentioning
confidence: 99%
“…More than 80% of the missing plastic qualifies as microplastic (MP, or plastics between 0.1 and 5 mm in length), and smaller (Cózar et al, 2014). These tiny particles might have been missed by historical sampling and are thus under-reported, or they might sink to the sediments (Woodall et al, 2014) or into deeper ocean water masses (Peng et al, 2018;Choy et al, 2019). Also, not all plastics are transported uniformly in the real ocean; e.g., the most significant concentrations of microfibers occurring far away from the most significant concentrations of other plastics in a recent survey of the Arctic (Cózar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Mariana subduction zone that occurs at convergent boundaries of the western edge of the Pacific Plate and the Philippine Plate is a unique biogeochemical hot spot. However, high concentrations of persistent organic pollutants in the trench sediments are affecting hadal ecosystems (Dasgupta et al, ; Peng et al, ). In fact, the production of hydrogen, methane, liquid sulfur, carbon dioxide, and minerals by geochemical reactions associated with water‐rock interactions can potentially fuel diverse microbial metabolisms in this zone (Hand et al, ; Stern et al, ).…”
Section: Introductionmentioning
confidence: 99%